Perfectionism and reactions to mistakes in competitive curling - Lizmore, M. R. (2013)
This study assessed the degree to which athletes (199 male, 144 female, M age = 30.78 years, SD = 7.93) with different profiles of perfectionism differed in terms of their emotional and cognitive responses to personal failure in low- and high-criticality situations in the sport of curling. Cluster analyses produced three clusters of athletes—labelled, healthy perfectionists, unhealthy perfectionists, and non-perfectionists—that closely resembled perfectionism profiles within Stoeber and Otto`s (2006) tripartite model of perfectionism. Results of a repeated measures MANOVA indicated that, irrespective of situation criticality, healthy perfectionists had lower anger/dejection and higher self-confidence/optimism following mistakes than unhealthy perfectionists (ps < .005). Results also indicated that, irrespective of perfectionism, athletes reported lower anger/dejection and higher self-confidence/optimism following mistakes in low- as opposed to high-criticality situations (ps < .005). Results reinforce the importance of considering personality and situational characteristics when assessing athletes` emotional and cognitive reactions to mistakes in sport.